2000
DOI: 10.1007/s11630-000-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aerodynamic noise generated from inclined circular cylinder

Abstract: Making clear the generation mechanism of fluid dynamic noise is essential to reduce noise deriving from turbomachinery. The analysis of the aerodynamic noise generated from circular cylinder is carried out numerically and experimentally in a low noise wind tunnel. In this study, aerodynamic sound radiated from a circular cylinder in uniform flow is predicted numerically by the following two step method. First, the three-dimensional unsteady incompressible Navier-Stokes equation is solved using the high order a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…However, the results of King and Barsikow [21] are closer to the trend obtained using γ = 6. The results are also compared with those obtained by Yamada et al [19] and Haramoto et al [20] for an inclined circular cylinder after being corrected by cylinder length by applying Eq. According to the independence principle the SPL should reduce more rapidly for higher yaw angles.…”
Section: Circular Cylindermentioning
confidence: 80%
See 2 more Smart Citations
“…However, the results of King and Barsikow [21] are closer to the trend obtained using γ = 6. The results are also compared with those obtained by Yamada et al [19] and Haramoto et al [20] for an inclined circular cylinder after being corrected by cylinder length by applying Eq. According to the independence principle the SPL should reduce more rapidly for higher yaw angles.…”
Section: Circular Cylindermentioning
confidence: 80%
“…For the circular cylinder, Figure 7 The results in Figure 7(a) are compared with those obtained by Yamada et al [19], by King and Barsikow [21] and by Haramoto et al [20] who measured the vortex shedding noise from circular cylinders for a similar Reynolds number range as that covered in the present investigations (see Table A.1 and Table A The reason that the present results are lower than those found in the literature could be that the aspect ratio L/D used in the current experiments is not high enough to allow the end effects to be neglected. Gowda found that the threedimensional flow produced by the cylinder free ends affected the Strouhal number of the vortex shedding produced by a circular cylinder in an air flow [33].…”
Section: Circular Cylindermentioning
confidence: 81%
See 1 more Smart Citation
“…Latorre Iglesias et al [14] assessed the effect of the angle of attack and flow speed on the aerodynamic cylinder noise and compared his results to the experimental studies of Yamada et al for AOA up to 45° [15], Haramoto et al up to 40° [16] and King and Barsikow up to 30° [17]. In a Reynolds range of 15.500 5 Re 5 39.000 and for 30°5 AOA 5 90°he found that amplitude and frequency of the aeolian tone and the overall sound pressure level decrease with declining AOA while the bandwidth of the spectral peak increases.…”
Section: Introductionmentioning
confidence: 99%
“…When a wind tunnel experiment is carried out with endplates, the sounds emitted from inclined circular cylinder depend on the diameter of the circular cylinder 1 . The objective of this paper is to clarify that phenomenon by both experiment (measurement of the sounds) and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%